Long Term Field Evaluation of Promising Subabul (Leucaeana leucocephala) Selections and Lines in Rainfed Conditions - Gupta, S.K.; Gupta, V.K.; Pathak, P.S.; Khan, T.A. (Indian Journal of Agroforestry, 2020)
Seven selections and seven promising lines of Leucaena leucocephala along with Var. K8 as a check were tested for their performance and productivity in four rotations from 1989-2007 in a randomized block design. Based on mean productivity of all the four rotations, S-24 ranked first with average productivity of 56.91 t ha-1 yr-1 followed by S-1 0 (56.18 t ha-1 yr-1 and K601 (51.85 t ha-1 yr-1). Highest productivity was obtained in second rotation (60.63 t ha-1 yr-1) followed by first rotation (43.13 t ha-1 yr-1), third rotation (39.5 t ha-1 yr-1 and fourth rotation (35.17 t ha-1 yr-1). Percent superiority for mean productivity was 28% for S-24, 26% for S-10 and 16% for K601 over K8.